Radiation Therapy for Residual or Recurrent Atypical Meningioma: The Effects of Modality, Timing, and Tumor Pathology on Long-Term Outcomes. Issue 1 (July 2016) - Sun, Sam Q.; Cai, Chunyu; Murphy, Rory K.J.; DeWees, Todd; Dacey, Ralph G.; Grubb, Robert L.; Rich, Keith M.; Zipfel, Gregory J.; Dowling, Joshua L.; Leuthardt, Eric C.; Simpson, Joseph R.; Robinson, Clifford G.; et al.
Abstract : BACKGROUND: Optimal use of stereotactic radiosurgery (SRS) vs external beam radiation therapy (EBRT) for treatment of residual/recurrent atypical meningioma is unclear. OBJECTIVE: To analyze features associated with progression after radiation therapy. METHODS: Fifty radiation-naive patients who received SRS or EBRT for residual and/or recurrent atypical meningioma were examined for predictors of progression using Cox regression and Kaplan-Meier analyses. RESULTS: Thirty-two patients (64%) received adjuvant radiation after subtotal resection, 12 patients (24%) received salvage radiation after progression following subtotal resection, and 6 patients (12%) received salvage radiation after recurrence following gross total resection. Twenty-one patients (42%) received SRS (median 18 Gy), and 7 (33%) had tumor progression. Twenty-nine patients (58%) received EBRT (median 54 Gy), and 13 (45%) had tumor progression. Whereas tumor volume ( P = .53), SRS vs EBRT ( P = .45), and adjuvant vs salvage ( P = .34) were not associated with progression after radiation therapy, spontaneous necrosis (hazard ratio [HR] = 82.3, P < .001), embolization necrosis (HR = 15.6, P = .03), and brain invasion (HR = 3.8, P = .008) predicted progression in univariate and multivariate analyses. Tumors treated with SRS/EBRT had 2- and 5-year actuarial locoregional control rates of 91%/88% and 71%/69%, respectively. Tumors with spontaneous necrosis, embolization necrosis, and no necrosis had 2- and 5-year locoregional control rates of 76%, 92%, and 100% and 36%, 73%, and 100%, respectively ( P < .001). CONCLUSION: This study suggests that necrosis may be a negative predictor of radiation response regardless of radiation timing or modality. ABBREVIATIONS: AM, atypical meningioma EBRT, external beam radiation therapy GTR, gross total resection LC, locoregional control OS, overall survival POE, preoperative embolization RT, radiation therapy SRS, stereotactic radiosurgery STR, subtotal resection